FRI0429 Distinct clinical and immunological picture of mctd patients with skin involvement. (12th June 2018) - Felis-Giemza, A.; Kontny, E.; Nałęcz-Janik, J.; Walkiewicz-Pielaszek, K.; Czuszyńska, Z.; Zdrojewski, Z.; Paradowska-Gorycka, A.; Olesińska, M.
Abstract : Background: Mixed connective tissue disease (MCTD) is characterised by the co-existence of systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), systemic sclerosis (SSc) and polymyositis/dermatomyositis (PM/DM) symptoms. The majority of patients have skin symptoms typical of at least one of the diseases making up the clinical picture MCTD. MCTD is characterised by an auto-reactive antibody response to RNP antigen and resultant formation of anti-U1RNP antibodies. Current knowledge on cytokine biology and their documented role in the pathogenesis of SLE, SSc and PM/DM suggests that also in MCTD some of them may affect clinical course, activity and/or degree of organ damage. Objectives: To compare clinical and immunological characteristics of MCTD patients with/without skin involvement. To identify clinical and immunological parameters increasing the risk for a specific (SLE- or SS-like) type of skin lesions and protecting against them. Methods: 79 MCTD patients based Kasukawa' MCTD diagnostic criteria were included. The patients were divided into groups based on the presence of skin lesions typical for a given MTCD component: SLE- SSc- and DM-specific. Results: Skin lesions were found in the majority of the MCTD patients (81%). The SLE-, SSc- and DM-specific skin symptoms were found in 54%, 61% and 5% of the patients, respectively. The group of patients with skin symptoms typical of DM was to small to distinguish it separately (4/79). The measures of disease activity (mean AI=10.6 vs 5.5; p=0.006) and MCTD-related damage (DI=4.1 vs 2.1; p=0.009) in patients with skin involvement were twice as high as in individuals with the intact skin. Furthermore, patients with skin involvement had higher mean serum concentrations of TNF-α (46.4 vs 2.3 pg/ml; p=0.013), and lower levels of IFN-γ (43.2 vs 120 8 pg/ml; p<0.001) than patients without any skin symptoms. The following clinical and immunological parameters were shown to be independently associated with specific types of skin involvement in MCTD patients on multivariate logistic regression analysis: Independent risk factors for: - SLE-like skin changes: increased ESR (OR=8.9, 4.47 and 2.6, respectively), higher AI scores and swelling of the hands, - SSc-like skin changes: higher DI scores (OR=1.522), and presence of anti-Ro60 antibodies (OR=15.903) Independent protective factors for: - SLE-like MCTD: chronic progressive course of the disease (OR=0.248) and higher serum concentration of IFN-γ (OR=0.988) - SSc-like MCTD: acute onset of the disease (OR=0.155). Conclusions: The course of MCTD in patients with skin involvement is more severe with specific panel of cytokine levels (increased TNF-α and decreased IFN-γ serum concentrations) is characteristic, as compared to patients with the intact skin. In patients with SLE-like skin lesions MCTD is more often multiphasic, its clinical activity and levels of inflammatory markers are higher while serum concentration of IFN-γ is diminished. Patients with SSc-like skin lesions more often have chronic MCTD, associated with more severe organ damage and elevated serum levels of TNF-α. Disclosure of Interest: None declared